Validation of Genetic Markers for AmpC, AAC, and RNR3 Genes in Potentially Present Pathogens Organisms in Fecal Sludge - Ummu Syauqah Al Musyahadah; Radhiyah Mardhiyah Hamid; Alricha Nasir (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The issue of sanitation and water pollution due to fecal waste has become a serious concern in Indonesia, particularly after it was revealed that approximately 70% of the community's drinking water sources are contaminated with human feces. Determining safe waste management requirements necessitates indicators confirming the contamination-free nature of the waste management methods. Pathogen testing indicators for fecal waste are highly diverse. The current standard testing is the culture-based method for microorganisms and microscopy observation for helminths. However, molecular detection tools for these pathogens can give higher sensitivity and specificity in a relatively shorter time of technical processing. In this research, we designed primers for molecular-based diagnostics on three pathogens exhibiting extreme survival capabilities under various environmental conditions. The species-coupled genes are AmpC for Escherichia coli, AAC for Mycobacterium tuberculosis, and RNR3 for Ascaris lumbricoides. The design of molecular-based biomarkers and their specificity tests were conducted using web-based bioinformatics programs to prevent unintended dimers. Ultimately, primers were validated by conventional gradient PCR on available positive controls and a sample from processed fecal sludge. The PCR validation test showed that the designed primers were validated to amplify the intended target with the right size without unspecific bands on the positive controls. Meanwhile, the AAC gene for E. coli was detected in the sample from the fecal sludge.